Socio-Professional Features of Employees of Cultural Institutions as Factors Shaping Their Professional Attitudes Towards the Place of Employment - Marcin Emil Cabak (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Performing professional work involves both the manifestation and the shaping of specific attitudes. Attitudes, in turn, influence behavior, which, in turn, shape organizational culture. Many contemporary publications emphasize the important role of cultural institutions in shaping the cultural life of Poles. Therefore, it seems interesting what attitudes towards work are displayed by their employees. Research Aim: The considerations in the article concern the professional attitudes of employees of cultural institutions and are aimed at diagnosing the relationship between the level of these attitudes and the socio-professional characteristics of this professional group. Method: The research was conducted using the survey method, using the survey technique in the second half of 2021, among 134 employees of various types of cultural institutions in the Lubelskie and Mazowieckie voivodeships. The deliberately random selection of the sample was made in such a way that institutions whose nature of activity falls within the adopted definition of a cultural institution were selected, while specific respondents were randomly selected. Results: The hypothesis was partially confirmed. Only a few relationships were found between the professional attitudes of the respondents and their social and professional characteristics. However, a differentiating influence of socio-professional factors was found both on the general level of attitudes and on their components. Conclusion: In the survey, employees of cultural institutions show a relatively high level of attitudes towards the work performed in general and towards its individual aspects, in particular, such as the atmosphere at work, adaptation of duties to skills and resources, and the proportion of work inputs to the results achieved. Significant exceptions are low levels of attitudes towards career advancement opportunities and earnings, which is an empirical confirmation of media reports and a hint for units institutionally organizing cultural life in Poland.